A implementação jurisdicional do direito fundamental à saúde sob uma ótica tópica e concretista - Carneiro, Bernardo Lima Vasconcelos (2015)
The dissertation has the desideratum to establish objective criteria for defining the exact extent of the material ambit of protection of the fundamental right to health in each case brought to the judiciary’s knowledge, in which the State is sued to pay medicine or treatment not provided by the public system of health. For this purpose, proceeds initially an investigation into the origins and historical development around the idea of "health", also stressing the key regulatory frameworks on the subject, highlighting the regulation determined by the Constitutional Charter of 1988. Next step, analyzes the phenomenon of judicialization of public policies, tracing the contours of its concept and identifying its elements and constitutive phases, in order to define the extent of judicial syndication of such policies, so that it proves to be legitimate in the face of the tripartite division of state powers and the democratic principle. Continuing, the dissertation studies the so-called "normative force of facts" which consists of influence that the factual reality has on the determination of the normativity content, including that of constitutional nature. At the point, after being examined the various theories that have studied the subject, based on those that have a topical and concretist character, it firms the understanding that the recognition of the right to health invoked in court depends on both the specific circumstances of the case that claims to solution to the socio-economic situation of the moment, and other factual variants not considered abstractly by the founding constitutional rule of that right, which, therefore, can not be understood as an absolute right to any medical service or the like. In the final chapter, with the assistance of the Economic Analysis of Law, are examined the conditioning suffered by the right to health due to the recognized financial contingency of the State, once understood the so-called "cost of rights" and the consequent need for decision makers undertake the so-called "tragic choices". Underlined the inadequacy of the theories of "reserves of possible" and "minimum existential" and collated, then, the tension between the “microjustice” of individual cases and social “macrojustice”, the dissertation proposes, at the end, practical requirements that must be present for the legal protection of the right to health may be granted in each of the judicialized cases.